(untitled) (Al-Ilmu, 2025)
This study aims to explore the integration of Islamic values into local traditions and their relevance to the practice of Islamic religious education in the community. This research uses a qualitative approach with a case study method, conducted through in-depth interviews, participant observation, and documentation of communities that still actively practice local traditions with Islamic nuances. The results show that local traditions such as selametan (celebration), Maulid Nabi (Prophet’s Birthday), tahlilan (religious gathering), and kenduri (celebration) contain strong Islamic values and can be effective media for religious learning. Religious and traditional leaders play a crucial role in the process of integrating these values through a down-to-earth cultural approach. However, this integration still faces obstacles, such as the lack of accommodation in the formal curriculum and resistance from some groups. Therefore, it is necessary to develop a more contextual model of Islamic religious education based on local wisdom to strengthen the understanding of Islamic values comprehensively.